Fibrillin-1 deficiency in the outer perichondrium causes longitudinal bone overgrowth in mice with Marfan syndrome. Issue 19 (14th May 2022) - Sedes, Lauriane; Wondimu, Elisa; Crockett, Brittany; Hansen, Jens; Cantalupo, Anna; Asano, Keiichi; Iyengar, Ravi; Rifkin, Daniel B; Smaldone, Silvia; Ramirez, Francesco
Abstract: A disproportionate tall stature is the most evident manifestation in Marfan syndrome (MFS), a multisystem condition caused by mutations in the extracellular protein and TGFβ modulator, fibrillin-1. Unlike cardiovascular manifestations, there has been little effort devoted to unravel the molecular mechanism responsible for long bone overgrowth in MFS. By combining the Cre-LoxP recombination system with metatarsal bone cultures, here we identify the outer layer of the perichondrium as the tissue responsible for long bone overgrowth in MFS mice. Analyses of differentially expressed genes in the fibrillin-1-deficient perichondrium predicted that loss of TGFβ signaling may influence chondrogenesis in the neighboring epiphyseal growth plate (GP). Immunohistochemistry revealed that fibrillin-1 deficiency in the outer perichondrium is associated with decreased accumulation of latent TGFβ-binding proteins (LTBPs)-3 and -4, and reduced levels of phosphorylated (activated) Smad2. Consistent with these findings, mutant metatarsal bones grown in vitro were longer and released less TGFβ than the wild-type counterparts. Moreover, addition of recombinant TGFβ1 normalized linear growth of mutant metatarsal bones. We conclude that longitudinal bone overgrowth in MFS is accounted for by diminished sequestration of LTBP-3 and LTBP-4 into the fibrillin-1-deficient matrix of the outer perichondrium, which results in less TGFβ signaling locally and improper GP differentiation distally.